Changes in levels of soluble T-cell activation markers, sIL-2R, sCD4 and sCD8, in relation to disease exacerbations in patients with systemic lupus erythematosus: a prospective study. - Spronk, P E (1994)
OBJECTIVES--To assess serial activation of T-cell subsets in relation to auto-antibody production and the occurrence of disease exacerbations in patients with systemic lupus erythematosus (SLE). METHODS--To study the possible role of T-cells in the pathophysiology of the disease, 16 consecutive exacerbations were prospectively studied in a cohort of patients with SLE, and serial plasma levels of sIL-2R, sCD4, and sCD8 preceding and during these exacerbations were determined. Levels of these molecules were related to total IgM and IgG, and anti-dsDNA. RESULTS--During major disease exacerbations (n = 6), levels of sIL-2R increased significantly (p < 0.001). Levels of sCD4 were predominantly in the normal range, whereas levels of sCD8 were frequently increased. No change in levels of both molecules could be detected in the period before the exacerbation. During minor exacerbations (n = 10), levels of sIL-2R remained stable. Levels of sCD4, however, tended to drop, whereas levels of sCD8 tended to rise. No correlations were found between sIL-2R, sCD4 or sCD8 on the one hand, and total IgM, IgG, or anti-dsDNA on the other. CONCLUSIONS--Levels of sIL-2R are increased, and rise before major exacerbations of SLE. Levels of sCD4 and sCD8, however, are not related to levels of sIL-2R, and do not reflect B-cell activation, nor disease activity during exacerbations of SLE. Thus for the clinical follow up of SLE measurement of levels of sCD4 or sCD8 is of limited value.